2022
DOI: 10.3389/fsurg.2022.756522
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Main Influencers of Surgical Efficiency and Variability Using Task-Level Objective Metrics: A Five-Year Robotic Sleeve Gastrectomy Case Series

Abstract: ObjectiveSurgical efficiency and variability are critical contributors to optimal outcomes, patient experience, care team experience, and total cost to treat per disease episode. Opportunities remain to develop scalable, objective methods to quantify surgical behaviors that maximize efficiency and reduce variability. Such objective measures can then be used to provide surgeons with timely and user-specific feedbacks to monitor performances and facilitate training and learning. In this study, we used objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Surgical data science, the field that has emerged from the analysis of OPIs, is young but includes exciting preliminary work in urology, general surgery, bariatrics, and thoracic surgery. 1,5,6 Early studies of OPIs (in previous literature referred to as automated performance metrics or objective performance metrics) came from laboratory and virtual environments. Fard et al 7 reported the use of machine learning analysis of OPIs during knot tying and suturing to predict surgeon expertise with >90% accuracy with immediate feedback.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Surgical data science, the field that has emerged from the analysis of OPIs, is young but includes exciting preliminary work in urology, general surgery, bariatrics, and thoracic surgery. 1,5,6 Early studies of OPIs (in previous literature referred to as automated performance metrics or objective performance metrics) came from laboratory and virtual environments. Fard et al 7 reported the use of machine learning analysis of OPIs during knot tying and suturing to predict surgeon expertise with >90% accuracy with immediate feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical data science, the field that has emerged from the analysis of OPIs, is young but includes exciting preliminary work in urology, general surgery, bariatrics, and thoracic surgery. 1,5,6…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…for partial nephrectomy, 10 Tousignant et al for sleeve gastrectomy, 11 and Metchik et al for lobectomy, 12 but no such work has been published for proctectomy. Through step segmentation, OPIs have enabled objective step-specific feedback to provide insights into surgical workflow, procedure complexity, surgeon skill and surgical outcomes.…”
mentioning
confidence: 99%